93.3k views
4 votes
I need help thank you​

I need help thank you​-example-1

2 Answers

3 votes

We want this:

3x^2 + 15x - 56 + (x - 8)^2

First, expand (x - 8)^2 using FOIL.

So, (x - 8)^2 = (x - 8)(x - 8).

(x - 8)(x - 8) = x^2 - 16x + 64.

We now add like terms.

3x^2 + 15x - 56 + x^2 - 16x + 64

4x^2 - x + 8

Done.

User Thomasvakili
by
5.6k points
5 votes

Answer:


4x^2-x+8

Explanation:

First expand
(x-8)^2.


(x-8)(x-8)=x^2-16x+64

Now Add:


(x^2-16x+64)+(3x^2+15x-56)\\(x^2+3x^2)+(-16x+15x)+(64-56)=\\4x^2-x+8

User Alessandro Togni
by
4.8k points